2000
DOI: 10.1016/s0166-1280(99)00400-5
|View full text |Cite
|
Sign up to set email alerts
|

Effective core potential ab initio calculations on main group heptoxides and large silicate systems

Abstract: The ab initio molecular structures for several main group heptoxides X 2 O nϪ 7 ; n 0; 2; 4 are calculated using effective core potentials at the HF and DFT (B3LYP) levels. Particular attention is given to the X-OX bond angle, as this structural parameter is a key feature for the study of both heptoxides and larger derivatives, such as polysilicate systems. The extent of the p-d interactions, which was found to be the main factor governing the magnitude of the X-OX angle in transition metal heptoxides, does no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Although the B3LYP DFT method is one of the most popular methods for calculating the quartz-water interface reaction mechanisms and kinetics (e.g., Becke, 1993;Civalleri et al, 1998;Davis et al, 1988;Ribeiro-Claro and Amado, 2000;Sefcik and Goddard, 2001;Teppen et al, 1994;Wallace et al, 2010;Walsh et al, 2000), recent studies have suggested that the B3LYP method may be deficient in the calculation of the energies of intermolecular interactions (e.g., Zhang et al, 2007;Zhao and Truhlar, 2007). Some new DFT methods (e.g., M05 and M06) have been developed specifically for the calculation of the energies of inter-molecular interactions.…”
Section: Methodsmentioning
confidence: 99%
“…Although the B3LYP DFT method is one of the most popular methods for calculating the quartz-water interface reaction mechanisms and kinetics (e.g., Becke, 1993;Civalleri et al, 1998;Davis et al, 1988;Ribeiro-Claro and Amado, 2000;Sefcik and Goddard, 2001;Teppen et al, 1994;Wallace et al, 2010;Walsh et al, 2000), recent studies have suggested that the B3LYP method may be deficient in the calculation of the energies of intermolecular interactions (e.g., Zhang et al, 2007;Zhao and Truhlar, 2007). Some new DFT methods (e.g., M05 and M06) have been developed specifically for the calculation of the energies of inter-molecular interactions.…”
Section: Methodsmentioning
confidence: 99%
“…For siliceous materials, a comprehensive study of 14 density functionals was reported [59], and the M05-2X functional was found to be most accurate for the optimized geometries and energetics. The basis set for these calculations was the all electron 6-31þG(d,p) chosen for the computational affordability for these relatively large silica clusters [60][61][62][63][64][65][66].…”
Section: Reactions and Methodsmentioning
confidence: 99%
“…As shown in Refs. [31,32], such choice of bases leads to good results for systems similar to one under consideration. Standard 3-21G basis was used for hydrogen atoms.…”
Section: Cluster Models and Quantum-chemical Calculationsmentioning
confidence: 99%